Exploring adolescent engagement in sexual and reproductive health research in Kenya, Rwanda, Tanzania, and Uganda: A scoping review - Hanna Chidwick; Andrea Baumann; Patricia Ogba; Laura Banfield; Deborah D. DiLiberto (Public Library of Science (PLoS), 2022)
Adolescent sexual and reproductive health (ASRH) in East Africa has prioritized research on the barriers to care, communication, and ASRH knowledge, attitudes, and practices. However, there is little research examining the extent to which meaningful adolescent engagement in research is achieved in practice and how this influences the evidence available to inform ASRH services. This review offers a critical step towards understanding current approaches to adolescent engagement in ASRH research and identifying opportunities to build a strengthened evidence base with adolescent voices at the centre. This scoping review is based on Arksey and O'Malley's (2005) framework, employing a keyword search of four databases via OVID: Medline, Global Health, Embase and PsycINFO. Two reviewers screened title, abstract and full text to select articles examining ASRH in Tanzania, Rwanda, Kenya, and Uganda, published between 2000 and 2020. After articles were selected, data was extracted, synthesized, and thematically organized to highlight emerging themes and potential opportunities for further research. The search yielded 1201 results, 34 of which were included in the final review. Results highlight the methods used to gather adolescent perspectives of ASRH (qualitative), the content of those perspectives (knowledge, sources of information, gaps in information and adolescent friendly services), and the overall narratives that frame discussions of ASRH (risky sexual behaviour, stigma, and gender norms). Findings indicate the extent of adolescent engagement in ASRH research is limited, resulting in a lack of comprehensive evidence, consistent challenges with stigma, little information on holistic concepts and a narrow framing of ASRH. In conclusion, there is opportunity for more meaningful engagement of adolescents in ASRH research. This engagement can be achieved by involving adolescents more comprehensively throughout the research cycle and by expanding the range of ASRH topics explored, as identified by adolescents.